Maintenance Tocolysis With Nifedipine in Threatened Preterm Labour: 2-Year Follow-up of the Offspring in the APOSTEL II Trial. Issue 2 (June 2017) - van Vliet, E.; Seinen, L.; Roos, C.; Schuit, E.; Scheepers, H.; Bloemenkamp, K.; Duvekot, J.J.; van Eyck, J.; Kok, J.H.; Lotgering, F.K.; van Baar, A.; van Wassenaer-Leemhuis, A.G.; et al.
Abstract : ( BJOG . 2016;123(7):1107–1114) Preterm birth is associated with an increased risk of perinatal morbidity and mortality, with the earlier the birth the greater the risk. Some of the complications resulting from preterm delivery lead to impairments with long-term consequences. Hence delivery postponement through tocolytic drug use is a management goal when women develop preterm delivery. Short-term tocolysis of 48 hours to allow administration of antenatal steroids has been found to be effective. However, several studies have shown that maintenance tocolysis beyond 48 hours does not significantly prolong pregnancy. The Assessment of Perinatal Outcome with Sustained Tocolysis in Early Labour (APOSTEL II) trial assessed maintenance tocolysis with nifedipine. This current follow-up study of APOSTEL II aimed to assess the effect of nifedipine maintenance tocolysis on neurodevelopment, as measured in 2-year-old infants whose mothers participated in the study.